(untitled) (Ustozlar uchun, 2025)
The article is devoted to the issue of analyzing students’ interest in English. It provides recommendations for determining students’ motivation to learn English, analyzing the factors affecting this process, and improving its effectiveness. During the analysis, aspects such as the age of students, level of education, the purpose of learning the language, and the teaching methodology provided to them were studied. The results showed the importance of using interactive lessons, multimedia tools, game approaches, and real-life examples to increase interest in English. This study will help educators and language teaching specialists to arouse students’ interest and form their need for language learning. The article also includes practical suggestions for using advanced approaches in language teaching.